(untitled) (Journal of the College of Basic Education, 2022)
The image fields and their kinetic signs are considered a semnatic presence for the sign communication and an expansion in the dialectical connection between the signifiers and thier signifieds carried out by the directive vision in order to produce concealing connotations that have their transitional essence through the ideas as being the data of the performance. Image coding seeks to broadcast the dual meaning within the multiple fields of performance. In order to understand the meaning amenating from these visual encryptions, there appears the need to examine the formation of these encryptions and how they transform into visual images. The researchers, in the introduction, addressed the problem of the research: how is the semantic image coding process is done in the theatrical show? The researchers tracked the signs and their codes to produce an integrated image system with its signifiers and signifieds to represent a fertile reference for the semantic encryption. The researcher founded a theoretical framework consisting of two sections: the first section(coding and semantics production) and the second section (the semantic coding in the directing experiments). The researchers derived a set of indicators that have been adopted in the analysis of the research sample, namely ( a group of texts have been integrated into one text and have been presented in the theatre in the black theatre method) according to the descriptive approach. The researchers then reached at a number of results such as ( the gestures, voice and movement contributed in making the signifiers an influential tool in the formation of the coding visual image, which produced a semantic spread in the theatrical show). The research ends with a list of sources and an abstract in English.